Physical activity and handgrip strength in patients with mild, moderate and severe haemophilia: Impacts on bone quality and lean mass - Pia Ransmann; Marius Brühl; Jamil Hmida; Georg Goldmann; Johannes Oldenburg; Frank Alexander Schildberg; Robert Ossendorff; Fabian Tomschi; Alexander Schmidt; Thomas Hilberg; Andreas Christian Strauss (PLoS ONE, 2025)
Background Patients with haemophilia (PwH) might be restricted in physical activity (PA) depending on the severity phenotype. It is well-known that PA affects overall health including bone quality. This study aims to evaluate the level of PA within the different haemophilia severity phenotypes and to elaborate on the interplay of PA in regard to bone quality (bone mineral density (BMD) and trabecular bone score (TBS)) as well as lean mass. Methods This investigation was part of a large prospective single-center cohort study examining the relation between haemophilia and osteoporosis registered at clinicaltrials.gov (ID: NCT04524481). PwH underwent a dual x-ray screening using Horizon™ to examine BMD, TBS, and lean mass. Step activity was tracked electronically for seven consecutive days after clinical examination, supported by a self-reported activity diary for seven days. Handgrip strength was examined as an overall fitness proxy. Results Data of 223 patients with either mild (N = 45), moderate (N = 46), or severe (N = 132) haemophilia A or B, aged 43.6 ± 15.6 years were analyzed. There was no significant difference in objective (p = 0.162) and subjective (p = 0.459) PA levels between severity phenotypes. The most frequent type of PA in all severities was walking (n = 72, 53.3%) and cycling (n = 60, 44.4%). Step activity positively correlated with TBS (rho = 0.202, p = 0.005) and lean mass positively correlated with BMD (rho = 0.309, p < 0.001). Handgrip strength correlated with BMD (rho = 0.361, p < 0.001) as well as TBS (rho = 0.221, p = 0.021) and lean mass (rho = 0.287, p = 0.003). Conclusion PA does not differ significantly between the severity phenotypes. The majority of PwH in all severity phenotypes performed low-impact PA, which is most likely insufficient to positively affect BMD. However, handgrip strength correlates with BMD and TBS. Despite restrictions in movement function or reduced BMD, it is of major importance to promote PA to maintain a healthy or even increase bone quality.